Hydrogen peroxide from cellular metabolism of cystine. A requirement for lysis of murine tumor cells by vernolepin, a glutathione-depleting antineoplastic. - Arrick, B A (1985)
The sesquiterpene lactone antineoplastic vernolepin acutely depletes murine tumor cell glutathione (GSH), and lyses the cells by an unknown mechanism that is enhanced synergistically by inhibition of GSH synthesis with buthionine sulfoximine (BSO) (Arrick et al. 1983. J. Clin. Invest. 71:258). We found here that lysis of P815 mastocytoma cells by vernolepin, with or without BSO, required cystine in the culture medium. Addition of catalase markedly suppressed vernolepin-mediated cytolysis in cystine-containing media, suggesting the involvement of hydrogen peroxide in the cytolytic action of vernolepin. Consistent with this, inhibition of tumor cell glutathione disulfide reductase with 1,3-bis(2-chloroethyl)-1-nitrosourea or inhibition of endogenous catalase with aminotriazole synergistically augmented cytolysis by vernolepin. Moreover, H2O2 was released by suspensions of P815 cells in cystine-containing buffer (63 pmol/10(6) cells X h). Omission of cystine reduced the rate of H2O2 accumulation 10-fold. No H2O2 was detected without cells. Cytolysis by vernolepin could be restored in cystine-deficient medium by several other disulfides, themselves noncytolytic, such as disulfiram and oxidized Captopril, as well as by cysteine. In contrast, withholding two other essential amino acids (leucine or tryptophan) or adding cycloheximide did not interfere with cytolysis by vernolepin. These results suggest that cellular uptake of disulfides of physiologic and pharmacologic interest may be followed by their intracellular reduction and autooxidation with generation of H2O2. This previously unrecognized source of intracellular oxidant stress may be an important component of injury to GSH-depleted cells.